2016
DOI: 10.1038/srep30546
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide impact of aerosol’s time scale on the predicted long-term concentrating solar power potential

Abstract: Concentrating solar technologies, which are fuelled by the direct normal component of solar irradiance (DNI), are among the most promising solar technologies. Currently, the state-of the-art methods for DNI evaluation use datasets of aerosol optical depth (AOD) with only coarse (typically monthly) temporal resolution. Using daily AOD data from both site-specific observations at ground stations as well as gridded model estimates, a methodology is developed to evaluate how the calculated long-term DNI resource i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 52 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…The studies covered by this review have unanimously identified clouds as the dominant source of short-term fluctuations in surface irradiance and photovoltaic power. Beyond that, aerosols have been shown to considerably affect irradiance variability as well, albeit on relatively large spatiotemporal scales and with an emphasis on concentrated solar power applications [160][161][162][163][164][165][166][167][168][169][170][171]. In consideration of extreme dust events, such as forest fires or sand storms (which can quickly generate large numbers of aerosols [172]), aerosol-induced small-scale irradiance variability could be non-negligible and further research is necessary in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The studies covered by this review have unanimously identified clouds as the dominant source of short-term fluctuations in surface irradiance and photovoltaic power. Beyond that, aerosols have been shown to considerably affect irradiance variability as well, albeit on relatively large spatiotemporal scales and with an emphasis on concentrated solar power applications [160][161][162][163][164][165][166][167][168][169][170][171]. In consideration of extreme dust events, such as forest fires or sand storms (which can quickly generate large numbers of aerosols [172]), aerosol-induced small-scale irradiance variability could be non-negligible and further research is necessary in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…This underestimation pattern of the peak AOD values is a consequence of imperfect forecasted meteorology and fading impact of the initial assimilation of MODIS AOD information on CAMS performance (MACC, 2015;Allen et al, 2013). Yet, despite this difference, the impact on the energy and SSR simulations is of the order of 10 % (see below description) in most cases (> 90 % of the spatial coverage), which highlights that CAMS 1-day forecasts are of great value and useful for solar energy potential planning and policies (Langerock et al, 2015;Charabi and Gastli, 2015;Kosmopoulos et al, 2015Kosmopoulos et al, , 2017Ruiz-Arias et al, 2016). Since the main inputs to the RTM are the AOD and the SZA, which can both be forecasted (CAMS AOD) and precalculated (SZA), the real time spatial and temporal estimation of the dust events impact on SSR is realistically feasible.…”
Section: Rtm Simulationsmentioning
confidence: 99%
“…The MODerate resolution Imaging Spectroradiometer (MODIS) sensors are among the primary instruments on board the polar orbit sun-synchronous NASA satellites Terra and Aqua (Salomonson et al, 1989). MODIS sensors have provided retrievals of AOD at 550 nm since February 2000 and June 2002 for Terra and Aqua satellites respectively.…”
Section: Modis and Calipsomentioning
confidence: 99%